STUDENTS AND NATIONAL POLITICS; PERCEPTION OF BANDUNG AND JAKARTA CITY STUDENTS OF NATIONAL INSIGHTS, RELIGIOUS MODERATION AND RELIGIOUS RADICALISM - Malau, Ruth Mei Ulina; Wulandari, Astri; Priastuty, Chairunnisa Widya (JWP (Jurnal Wacana Politik), 2024)
Indonesia is a multicultural nation with a variety of ethnic groups, religions, and faiths. This diversity can be an advantage and at the same time can cause horizontal conflict in society. Ideology and national politics owned by the Indonesian people are important as guidelines in the life of the nation and state within the framework of the Unitary State of the Republic of Indonesia. Students as one of the important elements in the journey of the Indonesian nation need to get attention related to the discourse of national politics. This research seeks to see students' perceptions related to national politics, religious moderation, and religious radicalism. The research was conducted using a quantitative approach and survey method. Respondents were university students in Jakarta and Bandung (200 people). This study aims to map the perceptions of students in Jakarta and Bandung towards national politics, religious moderation, and religious radicalism and to see whether there is an influence of understanding of national politics and religious moderation on religious radicalism among students in Jakarta and Bandung. The results showed that in students' perceptions of the understanding of national politics, religious moderation, and religious radicalism, the majority are in the moderate category or not good enough (average 55%). In addition, the influence of understanding nationalism and religious moderation on religious radicalism was also found to be 3.1%. This means that there is still a need to increase students' understanding in Jakarta and Bandung of national politics, religious moderation, and religious radicalism.